Respuesta :
[tex]\dfrac{c-5}{c^2-25}\\\\use:\ a^2-b^2=(a-b)(a+b)\\\\=\dfrac{c-5}{(c-5)(c+5)}=\dfrac{1}{c+5}[/tex]
For this case we have the following expression:
[tex] \frac{c-5}{c^2-5} [/tex]
To simplify the expression, the first thing to do is factor the denominator.
We have then:
[tex]\frac{c-5}{(c-5)(c+5)}[/tex]
Then, canceling similar terms we have:
[tex]\frac{1}{(c+5)}[/tex]
From here, we must find any value that should be excluded from the expression.
We must exclude values of c that make the denominator equal to zero.
We have then:
[tex] c+5=0
c=-5 [/tex]
Answer:
The simplified expression is:
[tex]\frac{1}{(c+5)}[/tex]
The value to be excluded from the expression is:
[tex] c=-5 [/tex]